Analisis Perbaikan Sistem Pentanahan Tower 70 kV pada Transmisi Wlingi - Blitar - Budi Eko Prasetyo; Ahmad Hermawan; Safira Azizah (Politeknik Negeri Malang, 2022)
High Voltage Air Line (in Indonesian known as SUTT) is defined as part of an electric power transmission network that is likely to be struck by lightning. This condition may lead to back flashover (BFO) phenomenon if the grounding value in the transmission is found to be high (>5 Ohms) and may also generate equipment failure. This research was intended to analyze the grounding improvement in tower T17, so that traveling-wave voltages may not result in failure of the main equipment at the substation, specifically the transformer. The value of the traveling wave at the substation was measured through simulation by means of the ATP Draw application in tower T17 to the substation. The grounding value may be reduced by increasing and widening the distance between the electrodes. The value obtained by modeling 4 electrodes with a distance of 0.5 meter was amounted to 1.73 Ohms. Furthermore, modeling 3 electrodes with a distance of 1 meter had successfully generated a value of 1.06 Ohm, and a value of 1.67 Ohm was also successfully obtained through modeling 2 electrodes with a distance of 2 meters. The ground resistance with a value of 67.05 Ohms that has not been repaired will lead to back flashover (BFO) caused by lightning strikes. However, this may be reduced properly with a lightning arrester which is capable of cutting the overvoltage at the substation, so that the voltage entering the transformer is below the BIL (Basic Insulation Level) value.